Epistatic Interaction between Genetic Variants in Susceptibility Gene ETS1 Correlates with IL‐17 Levels in SLE Patients. (24th April 2013) - Zhang, Jing; Zhang, Yan; Zhang, Lu; Yang, Jing; Ying, Dingge; Zeng, Shuai; Lee, Tsz Leung; Lau, Chak Sing; Chan, Tak Mao; Leung, Alexander Moon Ho; Mok, Chi Chiu; Wong, Sik Nin; et al.
Summary: T‐helper cells that produce IL‐17 (Th17 cells) are a subset of CD4 + T‐cells with pathological roles in autoimmune diseases including systemic lupus erythematosus (SLE), and ETS1 is a negative regulator of Th17 cell differentiation. Our previous work on genome‐wide association study (GWAS) identified two variants in the ETS1 gene (rs10893872 and rs1128334) as being associated with SLE. However, like many other risk alleles for complex diseases, little is known on how these genetic variants might affect disease pathogenesis. In this study, we examined serum IL‐17 levels from 283 SLE cases and observed a significant correlation between risk variants in ETS1 and serum IL‐17 concentration in patients, which suggests a potential mechanistic link between these variants and the disease. Furthermore, we found that the two variants act synergistically in influencing IL‐17 production, with evidence of significant genetic interaction between them as well as higher correlation between the haplotype formed by the risk alleles and IL‐17 level in patient serum. In addition, the correlation between ETS1 variants and IL‐17 level seems to be more significant in SLE patients manifesting renal involvement, dsDNA autoantibody production or early‐onset.